TIPE KONSUMEN MARKETPLACE BLIBLI.COM MENURUT TEORI HAUSEL - Abdi Baha, Mohamad; Popy Novita Pasaribu (Jurnal Visionida, 2023)
The rapid development of technology in economics and business is changing the patterns and lifestyles of consumptive humans towards the use of online shopping applications, shopping services via the internet that are easy and practical of course make consumers become accustomed to and continue to use them from the many online shopping applications of course each customer has his own experience in using related applications, this research also combines neuromarketing science. The study aims to obtain customer assessments of the use of the blibli.com online application by combining neuromarketing theory according to Hausel’s theory. This research uses quantitative methods with questionnaire data collection techniques and is processed through Microsoft Excel and SPSS applications. The results showed that marketplace consumers according to Hausel’s Limbic Type are Connoisseurs, Hedonists and Harmonists, while Blibli’s Limbic Map is balance. The domain name, Blibli.com, has a positive and significant effect on consumer preferences in the Blibli.com market place, although other variables do not have a significant effect, but overall the components have a positive effect on the total Y. The research explains that consumer preferences for the Blibli.com market place or e-commerce get a percentage of 77.7%.